Evaluation of Systems and Procedures for Affixing Paid Stamp Duty Markings with Printing Technology in 2020 (Case Study at the Kantor Pelayanan Pajak Wajib Pajak Besar Empat) - Dian Wahyudin; Indriani Rahayuning Tyas; Anwar Atmojo; Iin Andrayanti; Faizah Julina (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The system and procedure for affixing the Paid Stamp Duty mark using printing technology has so far been less effective. From the reporting method, it is not possible to know with certainty the number of banking documents that have been printed and affixed with the sign of Paid Stamp Duty by the printing company. This is due to the absence of a system that bridges the reporting of the issuance of banking documents printing permits. The tax account code and Deposit Type Code (KAP-KJS) 41161-100 for the deposit of Stamp Duty contain all Stamp Duty payments, both using printing technology and computerized systems, including companies that are not banking institutions. This study aims to evaluate the system and procedure for affixing the stamp duty mark in full with printing technology at the Kantor Pelayanan Pajak Wajib Pajak Besar Empat, the obstacles faced and the efforts made. This research approach uses descriptive qualitative with the type of case study research. Data collection techniques were carried out through in-depth interviews with 10 informants. The results of the study show: 1) Evaluation of the system and procedure for affixing the stamp duty sign in full has been carried out by the Kantor Pelayanan Pajak Wajib Pajak Besar Empat in accordance with the stages that must be passed and the criteria determined by still being guided by the applicable provisions and regulations, 2) Constraints actually exist when implementing systems and procedures that are currently still being carried out which are still manual and require a long and complicated process and make it difficult to supervise, 3) The efforts made are more to provide suggestions so that the results of the evaluation of the system and procedures for affixing customs duties the stamp duty can be taken into consideration in making decisions or policies in order to improve and perfect the systems and procedures that have been implemented so far